Selection of Natural Fiber for Hybrid Kevlar/Natural Fiber Reinforced Polymer Composites for Personal Body Armor by Using Analytical Hierarchy Process - Naveen, J.; Jawaid, M.; Zainudin, E. S.; Sultan, Mohamed T. H.; Yahaya, Ridwan B. (Frontiers in Materials, 2018)
Kevlar 29 is the most widely used synthetic fiber for personal body armour and they have been derived from petroleum based resources. Depletion of petroleum resources and the increase in awareness about the eco-friendly materials encouraged the researchers to explore the potential use of natural fiber as an alternative for synthetic fibers. Hybridization of natural fiber with synthetic fiber will results in unique properties which is difficult to obtain from the individual fibers. In this research Analytical Hierarchy Process (AHP) was used to identify the most suitable natural fiber to be hybridised with Kevlar 29 fiber as a reinforcement in the polymer composites for personal body armour. Fourteen natural fibers and seven criteria’s were selected and analysed for hybridization with respect to the personal body armours design specification. Cocos nucifera sheath which is a naturally woven fiber yields the highest priority vector and it was selected as a promising natural fiber for hybridization with Kevlar 29 for personal body armour. Eventually, sensitivity analysis was carried out to check the stability of the priority ranking.